Penyusunan Konsep Sustainable Village Melalui Analisis Anggaran Pendapatan dan Belanja Desa di Kabupaten Jember - Oktaviani, Siska Aprilia; Pratiwi, Berlina Yudha; Kurrohman, Taufik (Jurnal Akuntansi Terapan dan Bisnis, 2024)
This article is designed to develop the concept of a sustainable village through an in-depth exploration of the Village Revenue and Expenditure Budget (APBDes) in Jember Regency. The primary focus of this research is to understand how Village Funds can be configured to support the concept of a Sustainable Village. This study uses descriptive quantitative analysis methods by processing APBDes data from 223 villages in Jember Regency to form the concept of a sustainable village. The results indicate that villages allocating funds with a priority on infrastructure spending, such as Yosorati, Mulyorejo, and Darungan, are more likely to implement the concept of a sustainable village compared to villages with lower allocations in the same category. This article highlights the importance of integrating sustainability principles into the planning and budgeting of Village Funds to ensure that development not only improves current living quality but also preserves the environment for the future.